2018
DOI: 10.1007/s00249-018-1283-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of phototoxicity of protoporphyrin IX synthetic and extracted from ssp Rattus novergicus albinus rats toward murine melanoma cells

Abstract: Protoporphyrin IX (PpIX) is a precursor of heme synthesis and is known to be an active photosensitizer and precursor of photosensitizers applied in photodynamic therapy (PDT) and photodynamic diagnostics (PDD). On irradiation with visible light, PpIX undergoes phototransformation, producing photoproducts which may also be phototoxic and increase its efficacy. The mechanism of PpIX phototransformation depends on environmental characteristics and can be different in vitro and in vivo. In this paper, we present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…PpIX extracted from the Harderian glands of ssp Rattus norvegicus albinus rats (PpIX endogenous, PpIXe) is an adequate model of the native type ( 11 ). We have demonstrated that PpIXe possesses photodynamic activity toward Harderian gland tissue ( 12 ) and murine B16F-10 melanoma cells ( 13 ). Moreover, its phototoxicity is 10 times higher and its rate of internalization into the cell is 8-fold higher compared with the synthetic one ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PpIX extracted from the Harderian glands of ssp Rattus norvegicus albinus rats (PpIX endogenous, PpIXe) is an adequate model of the native type ( 11 ). We have demonstrated that PpIXe possesses photodynamic activity toward Harderian gland tissue ( 12 ) and murine B16F-10 melanoma cells ( 13 ). Moreover, its phototoxicity is 10 times higher and its rate of internalization into the cell is 8-fold higher compared with the synthetic one ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that PpIXe possesses photodynamic activity toward Harderian gland tissue ( 12 ) and murine B16F-10 melanoma cells ( 13 ). Moreover, its phototoxicity is 10 times higher and its rate of internalization into the cell is 8-fold higher compared with the synthetic one ( 13 ). This makes PpIXe not only an adequate model but also a promising PS for PDT and a fluorescence probe for FD.…”
Section: Introductionmentioning
confidence: 99%